Synthesis of polymeric microspheres containing inorganic nanoparticles - I. A. Gritskova; A. Yu. Gervald; N. I. Prokopov; Yu. M. Shiryakina; N. S. Serkhacheva (Тонкие химические технологии, 2011)
The basic types of morphology of composite polymeric microspheres are considered. Methods of synthesizing polymeric microspheres containing inorganic nanoparticles are generalized